Effect of VO43− substitution for PO43− on electrochemical properties of the Li3Fe2(PO4)3 cathode materials - Yang, Yonggang; Zhang, Yongguang; Hua, Zhengshen; Wang, Xin; Peng, Huifen; Bakenov, Zhumabay (Electrochimica Acta, 2016)
Abstract In this research, VO43− substitution was used to improve electrochemical properties of the Nasicon Li3Fe2(PO4)3 cathode material. The VO43− substitution resulted in formation of a homogeneous compound Li3Fe2(PO4)3-x(VO4)x in a composition range of x≤0.45; further introduction of VO43− led to precipitation of some other phases. It was shown that the VO43− substituted samples presented discharging capacity higher than that of bare non-substituted Nasicon and the reported Ti4+ and Mn2+ doped ones. The Li3Fe2(PO4)2.55(VO4)0.45 material exhibited excellent cycling stability and rate capability, and retained a capacity of 91.8mAhg−1 after 60 cycles at 2C charge-discharge rate. This value is one of the highest reported to date for the Li3Fe2(PO4)3 compound, and was about 48% higher than that of the latter. The electrochemical performance enhancements for the VO43− substituted samples were attributed to the reduction of charge transfer resistance, increase of electrical conductivity, and fast lithium ion diffusion behavior. Hence, the obtained results proved that the VO43− anion substitution for PO43− is a powerful technique to improve the electrochemical performance of the studied Nasicon compound.
Keywords: Lithium ion battery; Nasicon cathode; Li3Fe2(PO4)3; Mixed anion effect; Anion substitution